Comparison of Monopolar Electrosurgical Conization and the Loop Electrosurgical Excision Procedure in the Management of High-Grade Squamous Intraepithelial Lesion - Ding, Jun; Xu, Haiou; Xia, Lihua; Cao, Shanshan; Wu, Qing (Frontiers in Surgery, 2021)
Objectives: To compare the performance and outcomes of monopolar electrosurgical conization (MESC) or the loop electrosurgical excision procedure (LEEP) in the treatment of high-grade squamous intraepithelial lesion (HSIL). Methods: This retrospective study included 554 patients diagnosed with HSIL through biopsy. The study used either LEEP or MESC for cervical conization. Additionally, the medical records of these patients, including the basic information, status of the excision margin, cone depth, cone width, fragmentation, complication, and the results of a 6-month follow-up after conization, were reviewed. Results: Compared to MESC, LEEP had a significantly higher rate of positive endocervical margin (3.77 vs. 8.65%; p = 0.018), burn injury of the margin (4.90 vs. 10.38%; p = 0.016) and a lower rate of adequate cone depth (83.40 vs. 89.62%; p = 0.034). In addition, LEEP was significantly more likely to cause fragmentation (p = 0.000). There was, however, no significant difference in the rate of abnormal cervical cytology and positive high-risk HPV (hrHPV) between these two groups, 6 months after cervical conization. Conclusion: Both LEEP and MESC appeared to be equally effective in the clinical treatment of HSIL. Nonetheless, MESC resulted in a better pathological outcome with regard to the status of the margin, tissue fragmentation, and cone depth.